Induction of endothelial PAS domain protein-1 by hypoxia: characterization and comparison with hypoxia-inducible factor-1alpha. - Wiesener, MS; Turley, H; Allen, W; Willam, C; Eckardt, K; Talks, K; Wood, S; Gatter, K; Harris, A; Pugh, C; Ratcliffe, P; Maxwell, P (1998)
Hypoxia results in adaptive changes in the transcription of a range of genes including erythropoietin. An important mediator is hypoxia-inducible factor-1 (HIF-1), a DNA binding complex shown to contain at least two basic helix-loop-helix PAS-domain (bHLH-PAS) proteins, HIF-1alpha and aryl hydrocarbon nuclear receptor translocator (ARNT). In response to hypoxia, HIF-1alpha is activated and accumulates rapidly in the cell. Endothelial PAS domain protein 1 (EPAS-1) is a recently identified bHLH-PAS protein with 48% identity to HIF-1alpha, raising the question of its role in responses to hypoxia. We developed specific antibodies and studied expression and regulation of EPAS-1 mRNA and protein across a range of human cell lines. EPAS-1 was widely expressed, and strongly induced by hypoxia at the level of protein but not mRNA. Comparison of the effect of a range of activating and inhibitory stimuli showed striking similarities in the EPAS-1 and HIF-1alpha responses. Although major differences were observed in the abundance of EPAS-1 and HIF-1alpha in different cell types, differences in the inducible response were subtle with EPAS-1 protein being slightly more evident in normoxic and mildly hypoxic cells. Functional studies in a mutant cell line (Ka13) expressing neither HIF-1alpha nor EPAS-1 confirmed that both proteins interact with hypoxically responsive targets, but suggest target specificity with greater EPAS-1 transactivation (relative to HIF-1alpha transactivation) of the VEGF promoter than the LDH-A promoter.